Selection of Lignin Degrading Bacteria from Soil, Kitchen Waste, Leaf Litter, and Cow Dung Based on Lignin Peroxidase and Manganese Peroxidase Activities - Taruna Dwi Satwika; Dwiana Muflihah Yulianti; Galang Anahatta Hidayat; Afifah Mariana (Institut Pertanian Bogor, 2025)
Lignin is a complex chemical heterogeneous polymer that forms a physical barrier to lignocellulose's biological and chemical hydrolysis, making lignocellulosic biomass challenging to degrade. Ligninolytic microorganisms play an essential role in lignin degradation by producing extracellular enzymes. Lignin peroxidase and manganese peroxidase are enzymes that play a role in lignin degradation. Forty-one bacterial isolates have been isolated from soil, kitchen waste, leaf litter, and cow dung. However, the ligninolytic activity of these isolates has yet to be discovered. This research aimed to determine the ligninolytic ability of bacteria isolated from soil, leaf litter, kitchen waste, and cow dung based on lignin peroxidase and manganese peroxidase activity. The study was conducted stages: isolate recultured, qualitative and quantitative testing of lignin peroxidase activity based on degradation of methylene blue dye, and qualitative and quantitative testing of manganese peroxidase activity based on degradation of phenol red dye. A total of four bacterial isolates from soil (Tn9, Tn14, Tn16, and Tn17) and two bacterial isolates from cow dung (KS2 and KS5) showed qualitative and quantitative lignin peroxidase activity. Manganese peroxidase activity was also shown by four isolates from soil (Tn2, Tn6, Tn14, and Tn16), one isolate from kitchen waste (SD1), and one isolate from cow dung (KS5) both qualitatively and quantitatively. The nine bacterial isolates that showed lignin peroxidase and manganese peroxidase activity have potential as lignin-degrading biological agents. Keywords: bacteria, ligninolytic, peroxidase